2020
DOI: 10.1101/2020.08.07.241810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection, neuropathogenesis and transmission among deer mice: Implications for reverse zoonosis to New World rodents

Abstract: Coronavirus disease-19 (COVID-19) emerged in November, 2019 in China and rapidly became pandemic. As with other coronaviruses, a preponderance of evidence suggests the virus originated in horseshoe bats (Rhinolophus spp.) and likely underwent a recombination event in an intermediate host prior to entry into human populations. A significant concern is that SARS-CoV-2 could become established in secondary reservoir hosts outside of Asia. To assess this potential, we challenged deer mice (Peromyscus maniculatus) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 39 publications
8
69
0
5
Order By: Relevance
“…As compared to postmortem studies, animal experiments have provided detailed information on the neuroinvasive potential of SARS‐CoV‐2, 59‐61,63‐65 which revealed that the predominant target organs were the lung of infected animals at early time points, and variably, the brain at later time points 62,63 . The presence of the virus in CNS was found within neurons in different brain areas with a wide spectrum of neuropathology, well consistent with the reported clinical symptoms in COVID‐19 patients 65 .…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…As compared to postmortem studies, animal experiments have provided detailed information on the neuroinvasive potential of SARS‐CoV‐2, 59‐61,63‐65 which revealed that the predominant target organs were the lung of infected animals at early time points, and variably, the brain at later time points 62,63 . The presence of the virus in CNS was found within neurons in different brain areas with a wide spectrum of neuropathology, well consistent with the reported clinical symptoms in COVID‐19 patients 65 .…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with this, at least three autopsy studies have described brainstem abnormalities after SARS‐CoV‐2 infection 43‐45 . Brainstem infection with SARS‐CoV‐2 was also reported in an animal experiment, where viral antigen was present multifocally at the level of lateral sulcus nucleus, optic chiasm, hypothalamus, thalamic parabrachial nucleus, and ventral posteromedial nucleus culminating in the gustatory cortex 65 …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In experimental settings, non-human primates, ferrets, cats, dogs, deer mice and hamsters have been found to be susceptible to SARS-CoV-2 infection [2,3,4,5,6]. Moreover, ferrets, cats, deer mice and hamsters were able to transmit the virus via the air [2,4,5,6,7]. In domestic settings, both dogs and cats have been found to carry the virus, displaying very mild to more severe symptoms, respectively [7].…”
Section: Introductionmentioning
confidence: 99%